Legal and regulatory issues in human resources management - Sims, Ronald R.; Sauser, William I. (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
This edited book is intended to address the need for an updated look at the HRM legal and regulatory environment. Contrary to existing books which address legal issues in HRM from a narrower focus or specific issue (like sexual harassment, performance appraisal or employment termination), this book provides a comprehensive and in-depth look at legal issues, regulations and laws which govern all aspects of human resource management--recruitment, selection, placement, performance management (i.e., employee training and development), benefits and compensation--and specific issues such as job analysis, sexual harassment, and the like.The contributors to this book offer their insight derived from their own research and practical experience with the HRM legal and regulatory environment/world of work. More specifically, the contributors examine, analyze and discuss challenges, issues and opportunities related to HRM legal and regulatory issues and the implications for employees and their organizations while emphasizing the importance of navigating such laws and regulations to the employment cycle and toward sustainable competitive advantage in today's and tomorrow's organizations.
Keywords: Management -- Employee participation -- Law and legislation.; Employee selection -- Law and legislation.; Labor laws and legislation.; Personnel management.; Industrial relations.; Electronic surveillance -- Law and legislation.; Human capital -- Management.; Ombudspersons.; Business & Economics -- Human Resources & Personnel Management.; Personnel and human resources management.; elektronické knihy; electronic books